2022
DOI: 10.12998/wjcc.v10.i19.6341
|View full text |Cite
|
Sign up to set email alerts
|

Review of clinical characteristics, immune responses and regulatory mechanisms of hepatitis E-associated liver failure

Abstract: Hepatitis E virus (HEV) is the most common cause of acute liver failure (LF) and one of the most common factors causing acute injury in acute-on-chronic LF (ACLF). When HEV-related LF occurs, a series of changes take place in both the intrahepatic environment and extrahepatic microenvironment. The changed types and distribution of immune cells (infiltrating macrophages and increased lymphocytes) in liver tissue, as well the increased proinflammatory cytokines and chemokines in the blood, indicate that the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Luckily, many studies were trying to conquer these issues. Elevating in ammatory cytokines, alternation of innate and adaptive immunity in these patients indicated that host immune response, rather than HEV virus itself, is a key factor for the occurrence of HEV-ALF [21] . Gut microbiota and its metabolites was recently found to be involved in the change of immune system, may participating in the development of HEV-ALF [24] .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Luckily, many studies were trying to conquer these issues. Elevating in ammatory cytokines, alternation of innate and adaptive immunity in these patients indicated that host immune response, rather than HEV virus itself, is a key factor for the occurrence of HEV-ALF [21] . Gut microbiota and its metabolites was recently found to be involved in the change of immune system, may participating in the development of HEV-ALF [24] .…”
Section: Discussionmentioning
confidence: 93%
“…Our study found that HEV was the causative agent of ALF among about 65.0% of pregnant females in India, in contrast to 40.0% among non-pregnant individuals in the same country. Pregnancy is a unique situation, due to the alternation of immune system, hormone change (progesterone and oestrogen), pregnant females are more susceptible for progressing to HEV-ALF [19][20][21] , especially in the 2nd and the 3rd trimester or when infection is blamed for HEV GT1 [22] . Pooled incidence in our study also revealed that, in India, about 28.0% HEV infected non-pregnant individuals progressed to HEV-ALF, while this incidence was approximately 34.0% in pregnant individuals.…”
Section: Discussionmentioning
confidence: 99%